Circular Economy Adoption: The Mediating Role of Attitudes in the TPB (Theory of Planned Behavior) Model - Asgar, Asgar; Razak, Syaparuddin; Hidayati Darwis, Rahma (ILTIZAM Journal of Shariah Economics Research, 2024)
This study aims to enrich the understanding of circular economy adoption in rural areas using the Theory of Planned Behavior (TPB) as the foundational framework. Through the developed conceptual model, the study explores the mediating role of community attitudes towards circular economy adoption, by expanding attitude variables involving the dimension of caring for maslahah as an aspect of Islamic economics, beliefs, and knowledge. By collecting data from 200 respondents using Simple Random Sampling in the Barebbo District of Bone Regency, the analysis results using Partial Least-Structural Equation Modeling (PLS-SEM). This research reveals that beliefs and knowledge play a central role in shaping individual attitudes towards circular economy adoption in accordance with the principles of Islamic economics. The lack of attitude mediation effects between caring for maslahah as an aspect of Islamic economics, beliefs, knowledge related to circular economy adoption indicates that awareness of the benefits of such practices has not fully driven sustainable economic behavior. This study highlights that knowledge is the strongest force, motivating changes in economic, social, and environmental behavior with positive impacts across dimensions. The study provides a pioneering contribution to the literature, opening insights into the complex interaction between community attitudes and circular economic behavior in rural areas.